ADHD among young adults born at extremely low birth weight: the role of fluid intelligence in childhood - Lahat, Ayelet; Van Lieshout, Ryan J.; Saigal, Saroj; Boyle, Michael H.; Schmidt, Louis A. (Frontiers in Psychology, 2014)
Poor executive function (EF) has been linked to attention-deficit/hyperactivity disorder (ADHD). Children born at extremely low birth weight (ELBW; < 1000 grams) have been found to show both poor EF, as well as elevated levels of symptoms of ADHD. In the present study, we examined whether fluid intelligence moderates the link between birth weight and later ADHD symptoms by prospectively following a cohort of 179 survivors who were born at ELBW. When participants were 8 years-old, they were matched with 145 normal birth weight (NBW; ≥ 2500 grams) control participants. At age 8, fluid intelligence was measured, and during young adulthood (ages 22-26), participants’ self-reported levels of ADHD symptoms were examined. We found that ELBW survivors, who also showed poor fluid intelligence, had the highest rates of ADHD symptoms, and particularly, symptoms of inattention. These findings point to the importance of examining developmental trajectories that contribute to risk for psychopathology in those exposed to intrauterine adversity.